Desain Dan Implementasi Data Warehouse Untuk Proyek Dengan Pengeluaran Terbanyak Pada Pt Dian Mandiri - Rizki, Rizki Dwi Satria (JUSS (Jurnal Sains dan Sistem Informasi), 2025)
The data needed in a company is not possible if every year will not increase or increase, and data must continue to grow Data warehouse is very important to be implemented in companies in order to facilitate the analysis of data and produce consideration in making decisions. Data warehouse is very well known as an infrastructure, some applications can be run in a data warehouse such as CRM and DSS. Supporting technologies such as cloud computing are also needed to choose the service model and deployment model, data mart for each subsection, data warehouse utilization can help in business processes and data analysis, so it can help business owners to make basic decisions. Utilization of data warehouse is not only for large companies, startups can also apply data warehouse to be able to support business development. the application of data warehouse using MySQL and Pentaho Data Intergartion tools.